Knowledge, Beliefs and Practices on Menstrual Hygiene - Thapa, Pratibha (Namuna Academic Journal, 2025)
Menstrual health is one of the superstitious beliefs in our society. We are not aware of “Knowledge, Beliefs and Practices of menstrual hygiene.” The study was conducted inside the school of the Itahari sub-metropolitan city, of Sunsari, Nepal. The researcher has conducted this research to find out the knowledge, practice and beliefs of menstrual hygiene using cross-sectional descriptive research methodology. Despite being educated, we are practicing and believing in those traditional practices. Some do not even have proper knowledge regarding menstrual hygiene. There are different beliefs, practices and knowledge regarding menstrual hygiene which have affected students in their studies and participation in festivals and also they have not been able to speak up openly regarding their problem due to hesitation. The findings show that people still need to have knowledge and be aware of beliefs and practices. It shows that some of the respondents are satisfied and happy with the knowledge, practices and beliefs in the way they have been socialized whereas some of them are not satisfied and happy they are going through. So, it shows that the school has to have the subject of health, population and environment in the curriculum. This helps most of the students to be clearer and have proper knowledge about menstrual health which helps to bring changes and perceptions of people will change.